Rwanda : Fiduciary Assessment on a Proposed Credit - World Bank (Washington, DC, 2014)
A fiduciary assessment for the Rwanda Public Sector Governance PforR was carried out, taking into account recent PFM diagnostic reports and meetings and discussions with key officials in the proposed implementing agencies and other stakeholders. The assessment followed the Draft Guidance Notes on PforR Operations and requirements of OP/BP 9.00, Program for Results. The assessment used the four pillars approach of the Organisation for Economic Co-operation and Development Development Assistance Committee (OECD-DAC) to define the inherent risks in the procurement environment. In line with the Sector Board s practices manual, the potential FM risks for the various PFM elements are rated as low (L), modest (M), substantial (S), or high (H). The assessment is also mindful of the gaps that may exist between form (policies, laws, structures, instructions/manuals) and actual functionality or practices of the PFM system. Mitigation measures are proposed to reinforce the government s PFM reform efforts. Critical measures are included in the PAP.